Professional knowledge and MSD prevention: portrait of their transmission during training and the intervention perspective - Sylvie Ouellet; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
When training is being organized in enterprises where the work is considered as being repetitive and manual, the trainer is usually chosen from among experienced workers with recognized expertise. The study’s aim was to analyze the types of knowledge transmitted by worker-trainers to apprentices in a food-processing industry in order to prevent musculoskeletal disorders. The knowledge orally transmitted by the trainers was analyzed from audio recordings of the daily follow-up of the training given. The ergonomic approach developed in this study has shown that knowledge linked to health protection, and to the “why” of movements and the benchmarks, aren’t as easily transmitted as others. The complexity of the transmission phenomenon and the need to help worker-trainers in developing the competency for passing on this knowledge were demonstrated. Intervention scenarios are proposed.